New Organizational Responses, Innovations and Social Impacts of Covid-19 on Third Sector organizations in Campania Region - Gabriella Punziano; Suania Acampa; Rossella Sorrentino (Fuori Luogo)
Utilizing Mixed Methods and an interdisciplinary approach this article explains the main results of the NORISC-19 project that investigates the impacts of COVID-19 on Third Sector Organizations (TSOs) in Campania, Italy, highlighting their innovative responses and social impacts amidst the pandemic and ongoing Third Sector Reform. The study reveals TSOs' adaptation to digitalization, resilience, and innovative strategies to address social needs and regulatory changes. Key findings include the diverse impacts of Pandemy and Normative Reforms of the Sector on TSOs, their strategic adaptations, and the crucial role of digital transformation in ensuring service continuity and addressing emerging social challenges. The main findings prompt a broader reflection, offering insights into the nonprofit sector's adaptation during crises and contributing to more articulated reflections on a policy agenda for the future of TSOs.